Distribution of Myeloid-Derived Suppressor Cells in Rheumatoid Arthritis and Sjögren’s Syndrome - Ieva NARKEVICIUTE; Diana MIELIAUSKAITE; Zygmunt MACKIEWICZ; Irena BUTRIMIENE; Rita VILIENE; Irena DUMALAKIENE (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the distribution of myeloid-derived suppressor cells (MDSCs) in patients with primary or secondary Sjögren’s syndrome (SS) or rheumatoid arthritis (RA) in order to better understand MDSCs significance in the pathogenesis of these autoimmune diseases. Patients and methods: We examined the frequency and calculated absolute counts of overall MDSCs (human leukocyte antigen-antigen D related (HLA-DR)low/cluster of differentiation (CD) 33+/CD11b+) and monocytic MDSCs (HLA-DRlow/CD33+/CD11b+/CD14+) subset in peripheral blood samples of 23 RA (5 males, 18 females; mean age 57 years; range 41 to 81 years), 25 primary Sjögren’s syndrome (pSS) (1 male, 24 females; mean age 56 years; range 32 to 77 years), 17 secondary Sjögren’s syndrome (sSS) (1 male, 16 females; mean age 60 years; range 49 to 73 years) and 23 nonautoimmune sicca syndrome (nSS) (23 females; mean age 59 years; range 44 to 92 years) patients by flow cytometric analysis. Results: Analysis revealed that the frequency of overall MDSCs increased in RA group (46.5±3.4) compared with nSS group (35.6±3.2; p=0.0322). An increase of absolute count of overall MDSCs was most evident in both RA (4383±456.8) and sSS groups (3890±495.7) compared with pSS (2447±275.1; p=0.0002 and 0.0067) and nSS groups (2025±218.1; p<0.0001 and p=0.0012). The highest absolute count of monocytic MDSCs also manifested in RA group (195.4±39.0), compared with all the other groups (86.0±24.9; p=0.0002 [pSS], 128.5±53.4; p=0.0076 [sSS], 83.7±19.0; p=0.0136 [nSS]). Conclusion: To summarize, we have determined that the most prominent increase of both total and monocytic MDSCs was evident in RA and sSS groups, which leads us to believe that MDSCs are associated with rheumatic processes.